Nature's way of healing / Valerie Ross and Abid Amir - Ross, Valerie; Amir, Abid (Universiti Teknologi MARA Cawangan Pahang, 2019)
The sounds of nature evoke universal pleasure. Birds, flora and fauna create a symphonic band with wind and water resulting in perfect acoustic, temporal and spatial harmony that arouses a sense of calm and well-being, promoting health in humans. When the anxiety and stress of city-life takes a toll, medical intervention is sought. Nature's sonic healing powers are often forgotten. Recent scientific studies have ascertained the health benefits of nature sounds with growing interest among the medical fraternity regarding its use in intervention tools such as guided imagery, a technique which uses imagery in a positive and directed manner with an ultimate goal to bring about healthy changes in both the mind and the body. Applying an interdisciplinary practice-led methodology, this study created Bespoke Music and Narration for use as Guided Imagery to promote relaxation for pre-operative cardiac surgery patients. It extrapolates how images and sounds of nature from the Royal Belum State Park, reputed to houseone of the oldest rainforest in the world dating back 130 million years were captured and transformed into a sonic-visual landscape embodying original images, narration and music in a creative artefact of research entitled 'Nature's Way of Healing'.